Effects of daughter tiller removal on shoot and root growth of the parent tiller in Lolium perenne. Issue 2 (1st July 2022) - Robin, Arif Hasan Khan; Matthew, Cory
Abstract: Background: This study investigated the effects of daughter tiller removal on parent tiller development in Lolium perenne . Methods: Plants of L. perenne were grown hydroponically to allow separation of roots by phytomer position on the tiller axis and allowed to form two daughter tillers. In Experiment 1, adult daughter tillers were excised and effects on subsequent main tiller growth were observed for 16 days, on average. In Experiment 2, the growth of main tillers with or without daughter tillers was compared over 90–100 days. Two cultivars, 'Alto' bred from New Zealand germplasm and 'Aberdart' bred from United Kingdom germplasm were tested. Results: Excision of adult daughter tillers reduced the dry weight of older roots at the base of parent tiller axes and accelerated new phytomer appearance. Preventing tillers from forming daughter tillers by new tiller excision resulted in increased individual leaf and root dry weight in tillers without daughter tillers. Conclusions: The data indicated that daughter tillers contributed substrate for root development of their parent tillers. The presence of daughter tillers reduced the size of their main tiller but greatly enhanced whole plant yield. Abstract : The contribution of parent and daughter tillers to the growth of each other was studied by daughter tiller excision in perennial ryegrass. Growth of daughters was slowed by contribution to parent tiller roots, while facilitation of daughter establishment reduced parent size. However, daughter–parent units were much larger than solo parent units.